Changes in behavior fueled by digital learning - Mokhtar, Norashikin; Ismail, Mohd Faiz; Nik Mat, Nik Mahfuzah; Ahmad, Irma (Universiti Teknologi MARA, Negeri Sembilan, 2025)
The rapid integration of digital technologies into education has triggered significant shifts in human behaviour. Digital learning, through its personalised platforms, interactive tools, and data-driven insights, has reshaped how students engage with content, educators, and their learning strategies. These changes are not only evident in academic contexts but also extend to health behaviours, suggesting a broader impact on human decision-making and motivation. Ranging from mobile applications to virtual classrooms has shown positive effects on student motivation and learning outcomes. Although other factors often mediate the relationship between digital learning and motivation, research has consistently indicated that educational technologies help improve learner engagement. For instance, Noor et al. (2022) found that tools such as educational apps and animated videos help stimulate students’ interest, indirectly enhancing their academic performance and mindset. One of the most transformative aspects of digital learning is the ability to personalise the learning experience.